بن يوسف بن خدة والقضايا التي شلت المؤسسات الانتقالية للثورة الجزائرية 1956-1962م - بن يونس احلام; لعلاوي حسناء; اشراف: سيد علي احمد مسعود (كلية العلوم الانسانية و الاجتماعية, 2025)
تتناول هذه المذكرة دور بن يوسف بن خدة في الثورة الجزائرية خلال الفترة بين 1956 و1962، مع التركيز على القضايا التي أثرت بشكل كبير على المؤسسات الانتقالية للثورة الجزائرية. وقد حاول بن يوسف بن خدة، الذي شغل مناصب مهمة داخل الحكومة المؤقتة للجمهورية الجزائرية، أن يواجه التحديات التي ظهرت بعد استقلال الجزائر. يتناول البحث بشكل خاص الأزمات السياسية والإدارية الداخلية التي شلت فعالية المؤسسات الانتقالية، والتي كانت مرتبطة بالصراع بين القوى السياسية والعسكرية داخل جبهة التحرير الوطني، وكذلك الضغوط الخارجية، مثل المفاوضات مع فرنسا. كما يُبرز المذكرة كيفية تأثير هذه القضايا على استقرار النظام السياسي في مرحلة ما بعد الاستقلال. الكلمات المفتاحية: بن يوسف بن خدة - المؤسسات الانتقالية - جبهة التحرير الوطني - الثورة الجزائرية - المفاوضات مع فرنسا. This thesis addresses the role of Ben Youssef Ben Khadda in the Algerian Revolution between 1956 and 1962, focusing on the issues that significantly affected the transitional institutions of the Algerian Revolution. Ben Youssef Ben Khadda, who held key positions within the Provisional Government of the Algerian Republic, sought to tackle the challenges that arose after Algeria's independence. The research specifically explores the internal political and administrative crises that paralyzed the effectiveness of the transitional institutions, which were linked to the conflict between the political and military factions within the National Liberation Front (FLN), as well as external pressures, such as negotiations with France. The thesis also highlights how these issues impacted the stability of the political system in the post-independence phase. Keywords: Ben Youssef Ben Khadda, transitional institutions, National Liberation Front, Algerian Revolution, negotiations with France.